Medication adherence : software development for anticoagulant medicine smart-packs - Chua, Ming Zhou (Nanyang Technological University, 2020)
As technology becomes ubiquitous in today’s society, professionals in various sectors such as healthcare are leveraging it to resolve problems and better the quality of treatment patients receive. Amongst these issues, medication non-adherence has been a costly one not only economically to the parties involved, but also to the well-being of the patients. The rise of technology usage in the healthcare sector has brought on an abundance of mobile applications and Internet of Things (IoT) devices serving both patients and healthcare professionals. This trend resulted in a solution that was developed to promote medication adherence through reminders while detecting pill consumption with an Electronic Medication Packaging (EMP). CorrectPill, an Android application published on the Google Play Store, was capable of scheduling medication reminders as well as transmitting adherence information from a paired Bluetooth smart blister pack to the cloud-hosted server database. While most solutions focus solely on promoting medication adherence, this solution does so while providing adherence monitoring capabilities as medication consumption captured by the Android application are sent to the database and may be retrieved by other clients. This project updates the prior implementation by modifying CorrectPill to new medication requirements. Necessary alterations were made to backend resources as well as the firmware to ensure that medication reminders and pill detection remained accurate following the newer Android releases. Besides accuracy and reliability, simplicity was a core tenet to providing an adherence solution applicable to users from all walks of life. Hence, former features that complicated the User Interface (UI) were revised or removed to present a cleaner experience for users. This project was later tested for feasibility in clinical trials through repeated feedback and revision.